2006
DOI: 10.1111/j.1600-0463.2006.apm_353.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of goblet cell‐ and mucin glycosylation‐related genes in the intestinal epithelium during infection with the nematode Nippostrongylus brasiliensis in rat

Abstract: Intestinal nematode infection induces marked goblet cell hyperplasia and mucus secretion, but the mechanisms of regulation of the changes still remain to be elucidated. In the present study, epithelial cells were isolated from the rat small intestine at various times after Nippostrongylus brasiliensis infection, and the levels of expression of goblet cell- and mucin glycosylation-related genes were estimated by semi-quantitative reverse transcription (RT)-PCR. Among the genes investigated, mucin core peptide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…Both cell types are known to contain and secrete extremely potent bioactive molecules, and while there has been considerable interest in the role of mast cells in the past, more recently attention has focused on the role of goblet cells. This has been stimulated by the realization that mucus comprises a range of molecules with different properties (Ishikawa et al, 1993), and that the qualities of mucus change during intestinal nematode infections (Yamauchi et al, 2006). Candidate molecules that have been singled out and have attracted attention recently include those among the mucus molecules themselves (Muc2 gene products; Webb et al, 2007) and molecules contained within the mucus (RELMb/ FIZZ2 (Artis et al, 2004) and the lectin encoded by the Intellectin-2 gene (Pemberton et al, 2004;Nair et al, 2006)).…”
Section: Discussionmentioning
confidence: 99%
“…Both cell types are known to contain and secrete extremely potent bioactive molecules, and while there has been considerable interest in the role of mast cells in the past, more recently attention has focused on the role of goblet cells. This has been stimulated by the realization that mucus comprises a range of molecules with different properties (Ishikawa et al, 1993), and that the qualities of mucus change during intestinal nematode infections (Yamauchi et al, 2006). Candidate molecules that have been singled out and have attracted attention recently include those among the mucus molecules themselves (Muc2 gene products; Webb et al, 2007) and molecules contained within the mucus (RELMb/ FIZZ2 (Artis et al, 2004) and the lectin encoded by the Intellectin-2 gene (Pemberton et al, 2004;Nair et al, 2006)).…”
Section: Discussionmentioning
confidence: 99%
“…spiralis , T. muris and H . polygyrus 76, 77, 78, 79. It has yet to be determined whether these changes occur as a result of the inflammatory environment or to resolve the infection; clearly more research is required to define the precise role of mucin glycans.…”
Section: Gi Nematode Infection and Alterations In Mucin Glycomementioning
confidence: 99%
“…Most of our current understanding of the central role that mucin glycosylation plays during inflammatory threat has come from challenging rodents with infectious agents,71, 77, 78 and there are data to suggest that during GI nematode infections, there are multiple changes in the expression of glycosyltransferases, the enzymes responsible for the synthesis of the glycan chains 75. Yamauchi et al77 have demonstrated that by day 2‐3 of T. spiralis infection, there is an increase in α‐2‐3‐sialyltransferase IV. Additionally, during maturation of T. spiralis, there is also an induction of 3‐0 sulphotransferase‐1 expression in the intestine that peaks at day 14 post‐infection and falls only when parasite expulsion occurs 77.…”
Section: Gi Nematode Infection and Alterations In Mucin Glycomementioning
confidence: 99%
See 1 more Smart Citation
“…Mucin hypersecretion contributes to expulsion of nematodes and trematodes from the gastrointestinal tract (Nawa et al, 1994;Seo et al, 2003). The expression and regulation of mucin-related (MUC) genes were reported in rodents infected with intestinal nematodes, including Trichinella spiralis and Nippostrongylus brasiliensis (Shekels et al, 2001;Yamauchi et al, 2006).…”
mentioning
confidence: 99%